1965
DOI: 10.1083/jcb.27.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes in the Rat Sciatic Nerve Following Crush

Abstract: Peripheral nerves undergoing degeneration are favorable material for studying the types, origins, and functions of lysosomes. The following lysosomes are described: (a) Autophagic vacuoles in altered Schwann cells. Within these vacuoles the myelin and much of the axoplasm which it encloses in the normal nerve are degraded (Wallerian degeneration). The delimiting membranes of the vacuoles apparently form from myelin lamellae. Considered as possible sources of their acid phosphatase are Golgi vesicles (primary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
2

Year Published

1967
1967
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(103 citation statements)
references
References 39 publications
5
96
2
Order By: Relevance
“…103 The scarcity of lysosomes in axons may suggest that mitochondrial degradation preferentially occurs in the soma. While it may take days for axonal transport to deliver an organelle to the soma for degradation, rapid elimination of dysfunctional mitochondria is probably critical for protection of neurons against oxidative damage and degeneration.…”
Section: Mitophagy In Neuronsmentioning
confidence: 99%
“…103 The scarcity of lysosomes in axons may suggest that mitochondrial degradation preferentially occurs in the soma. While it may take days for axonal transport to deliver an organelle to the soma for degradation, rapid elimination of dysfunctional mitochondria is probably critical for protection of neurons against oxidative damage and degeneration.…”
Section: Mitophagy In Neuronsmentioning
confidence: 99%
“…However, the removal process of the myelin sheath during Wallerian degeration is not completely clear and there is still considerable controversy as to the type of cells involved in the removal. Many investigators have suggested that only Schwann cells (9,12), or macrophages (4,6,17) or both cell types (5,13,15) participate in the removal of the myelin sheath during nerve degeneration. Some investigators (5,12,13,19) found that Schwann cells and macrophages contained myelin fragments, but the source of the myelin fragments within the Schwann cells is still uncertain.…”
mentioning
confidence: 99%
“…As the mitochondria are unstained with FRAP [11], the reason for the mitochondrial FRAP-like reaction is not known. After peripheral nerve crush, degenerated axonal mitochondria exhibited precipitation of lead phosphate [10]. Several types of axon terminals showed FRAP reactivity: one type consists of small round, slender, dark sinuous and large scalloped terminals with packed clear synaptic vesicles, and the other consists of larger roundish terminals with less packed clear synaptic vesicles and many mitochondria.…”
Section: Discussionmentioning
confidence: 99%